Fundamental Rights and the Obligation to Publicly Disclose Information on Tax Strategy - Szymacha, Adam (Journal of Finance and Financial Law, 2021)
The aim of the article: The presented study concerns the problem of violations of fundamental rights caused by the law regulation contained in art. 27c of the Corporate Income Tax Act in Poland. This regulation provides obligation to publish information about introduced tax strategies. Yet, it may endanger many human rights and this article focuses on two of them – the right to remain silent, and the right of privacy. The aim of this article is to make an analysis of the standards presented by the Court of Justice of the European Union and the European Court of Human Rights. Additionally, the standard presented by the Polish Constitutional Court is presented. Methodology: To decode these standards the comparative law method is used. Especially the case laws of these courts are presented and additionally, they are completed by the comparison of the acts that concern similar law institutions but come from different lawmakers. Results of the research: The results of the study do not provide a clear answer. However, they do allow for an approximation of the issue of possible violations of fundamental rights by the analyzed regulation. It is very likely that the analyzed regulation violates the right to remain silent and it is even close to certainty that the analyzed laws violate the right to privacy. The problem is not only the interference in these rights, but in its character as well. Under certain circumstances, interference with fundamental rights is acceptable but must be proportionate. Examined laws are only explained in terms of budgetary balance and the academic world points out that the purpose of this type of regulation is mainly of administrative convenience. This is far too little to consider this interference with fundamental rights imperative.